2017
DOI: 10.3329/bjms.v16i3.32871
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Diaphragmatic Mobility Assessment Using a Real Time Ultrasound Among Non-Specific Low Back Pain.

Abstract: Background and Objective: Ultrasound measurement of Diaphragmatic Mobility (DM) has been shown to be a reliable measurement tool among healthy subjects. However, the measures of reliability are needed prior to clinical use of this device among Non-Specific Low Back Pain (NS-LBP). Therefore, the aim of the study was to investigate the relative and absolute reliability of DM using Real Time Ultrasound (RTUS) among subjects with NS-LBP. Materials and Methods: Nine subjects with NS-LBP (23.33 ± 1.58) years old wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…It is an indicator to assess whether the body could inhale enough gas to meet the needs during each inspiration, which could refect the lung ventilation capacity. Te intrarater reliability of the diaphragm excursion measurement by M-mode ultrasound in this study was consistent with Mohan et al's study [42], which reported excellent ICC values (0.964 and 0.92, respectively), but inconsistent with Gram et al's study (ICC values range from 0.65 to 0.69) [43]. Te reason for this distinction between our study and Gram et al's study might be due to diferent interval measurement periods.…”
Section: Discussionsupporting
confidence: 92%
“…It is an indicator to assess whether the body could inhale enough gas to meet the needs during each inspiration, which could refect the lung ventilation capacity. Te intrarater reliability of the diaphragm excursion measurement by M-mode ultrasound in this study was consistent with Mohan et al's study [42], which reported excellent ICC values (0.964 and 0.92, respectively), but inconsistent with Gram et al's study (ICC values range from 0.65 to 0.69) [43]. Te reason for this distinction between our study and Gram et al's study might be due to diferent interval measurement periods.…”
Section: Discussionsupporting
confidence: 92%
“…The distance between these two points corresponded to DM. This method of assessment has been considered reliable and valid (Mohan, Hashim, Md Dom, Sitilerpisan, & Paungmali, ; Toledo, Kodaira, Massarollo, Pereira, & Mies, ; Yamaguti et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Eight included articles measured the thickness [ 35 , 38 41 , 43 , 48 , 52 ], nine measured excursion [ 36 , 37 , 42 45 , 47 , 49 , 52 ], three measured stiffness [ 23 , 24 , 26 ], two measured strain [ 46 , 47 ], and one measured motion velocity of diaphragm [ 50 ]; one included study measured the thickness [ 51 ], and one measured stiffness of intercostal muscles [ 25 ]; one included study measured the thickness of transverse abdominals and internus obliquus with different approaches [ 34 ]. The details of each measurement approach are described in Supplementary File-S 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Two included studies [ 42 , 43 ] consistently reported sufficient within- (ICC = 0.74–0.76) and between-day intra-rater reliability (ICC = 0.78–0.92) of using M-mode USG to measure the right hemidiaphragm excursion. The COSMIN ratings of both studies were doubtful, and the quality of evidence was very low.…”
Section: Resultsmentioning
confidence: 99%